ANIMAL POETICS IN BRITISH CONTEMPORARY POEMS: FORGING INDIVIDUALÃ¢â¬â¢S CONCERN ABOUT ENVIRONMENTAL CONSERVATION - Yulianto, Henrikus Joko (Language Circle: Journal of Language and Literature, 2012)
In times of todayÃ¢â¬â¢s changing global world, each of us needs to have a kind of steel armor to shield us from any threatening and daunting global impacts. Yet, we cannot just sit still or stay indolently to let any hazards take over or disrupt the living concordance and convenience. In case of environmental issues for instance, problems such as deforestation, pollution, global warming still become prevalent issues that people are coping up with. Literature as one social and cultural product should play roles in evoking peopleÃ¢â¬â¢s understanding about the importance of conserving and preserving our environment. It is through ecocriticism or a criticism that harmonizes ecology and literary criticism that literature can participate in disseminating the values of green living. Poetry is one of literary genres that best describes oneÃ¢â¬â¢s vision of environment; contemporary British poetry is another example of the work that remarkably captures the sight and vision of the poets about problems related to the conservation of wildlife in their respective habitats.